Local Wisdom Preservation in Inter-Ethnic Weddings in Cimahi City's Batak Karo Community - Lili Halimah; Heni Heryani; Eva Enzelia Barus (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
North Sumatra province has a variety of unique cultures, one of which is marriage tradition and wedding ceremony. Marriages—containing noble values and norms of the purpose of life—are legally bound in traditional wedding ceremonies so the marriage will be safe. In Batak Karo tribe, one of the tribes in North Sumatra, the ideal marriage is the one that follows the rimpal tradition, which means that a man will be recommended to marry the daughter of his mother's brother. In its development, inter-ethnic marriages provide a solution to overcome the problems of unideal marriage. This article describes the condition when the ideal marriage is not fulfilled. The study used qualitative approach in the Karo Persadaan community in Cimahi City, West Java, involving the role of religious and traditional leaders. The results of the study show that inter-ethnic weddings in the Batak Karo community are allowed but with complete customary procedures as performed in ideal wedding ceremonies to preserve their local wisdom and prevent the Batak Karo identity from being extinct overseas.